(untitled) (Informatica, 2024)
Complex equipment disassembly tasks often require a group of people to complete, and the same time satisfying various resource constraints. This paper proposes an improved elite genetic algorithm (IGA) for the asynchronous parallel disassembly (APD) problem with the task priority, disassembly workspace interference and human resource constraints. The feasibility and effectiveness of the algorithm are verified through a hydraulic turbine hoisting and disassembling task instance. Results show that compared with classical algorithms (ACO&AGA) applied in APD, the proposed method is feasible and effective, and also has practical guiding significance for planning complex disassembling projects.